Spectrum of ascending aortic aneurysms at a peri-urban tertiary hospital: an echocardiography-based study - Meel, Ruchika; Hasenkam, Michael; Goncalves, Ricardo; Blair, Kelly; Mogaladi, Shungu (Frontiers in Cardiovascular Medicine, 2023)
Thoracic ascending aortic (TAA) aneurysms are an important cause of disability and death and require early detection for effective management. Currently, there is a paucity of data from Africa pertaining to TAA aneurysms. This study describes the spectrum of TAA aneurysms at a peri-urban tertiary hospital. A descriptive retrospective study based on clinical and echocardiographic imaging data of patients with TAA aneurysms from October 2017-October 2022. Advanced strain imaging was performed to measure left ventricular (LV) basal, apical, and global longitudinal strain as well as circumferential strain (CS) of the ascending aorta as a proxy measurement of aortic compliance. The study comprised 139 cases of TAA aneurysms (52.5% females) with a mean age of 50±14.8 years with 45 age and gender matched controls. Most cases (95%) were of African ethnicity. The main etiologies were hypertension (41.7%), HIV (36.6%), connective tissue disease (10.7%), congenital (2.2%) and mixed pathologies (8.6%). Two-thirds of patients (69.7%) presented in heart failure, 10% presented with aortic dissection. Thirty percent of patients were classified as New York Heart Association (NYHA) class I, 59.7% NYHA II, 8.6 % NYHA III and two patients NYHA class IV. Echocardiography revealed enlarged aortic dimensions compared to controls (P<0.001). TAA aneurysms were complicated by severe aortic regurgitation (AR) in half (50.3%) of patients, moderate AR in 25.8%, and mild AR in 14.3%. The mean LV ejection fraction (46.9±12.7%) was reduced compared to controls (P<0.001). Aortic CS was reduced compared to controls (4.4(3.2-6.2) % vs 9.0(7.1-13.4) %, P<0.001). Aortic stiffness was higher in the aortic aneurysm group compared to controls (15.39±20.65 vs 5.04±2.09, P=0.001). LV longitudinal strain (-13.9±3.9% vs 18.1±6.7%), basal CS (-13.9±5.6 % vs -17.9±5.8%) and apical CS (-8.7±8.5% vs -30.6±3.8%) were reduced compared to controls (P<0.001). Most patients were on diuretic and anti-remodeling therapy. Surgery was performed in 29.4% and overall mortality was 7.9 %. Mortality for acute aortic dissection was 40%. TAA aneurysms associated with hypertension and HIV are common in this predominantly African female population and are associated with considerable morbidity and mortality. Two-dimensional echocardiography and advanced strain imaging are potential tools for detecting and risk stratifying TAA aneurysms.